Tinted glass sees the clear diagnosis: sign of ovarian mucinous cystadenoma - Shrivastava, Amit; Saxena, Ashima; Jindal, Gunjan; Garg, Preeti; Batish, Yoshita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Ovarian mucious cystadenoma are commonly affecting the women with age group of 20-40 years and benign in nature. Due to varying cystic contents within heterogeneous signal intensities are noted on MRI looks like stained-glass window sign and acts as a distinguishing characteristic. Recognizing the stained-glass window sign enables timely and accurate care of ovarian neoplasms and increases diagnostic confidence.